The perforin mediated apoptotic pathway in lung injury and fibrosis. Issue 12 (24th November 2004) - Miyazaki, H; Kuwano, K; Yoshida, K; Maeyama, T; Yoshimi, M; Fujita, M; Hagimoto, N; Yoshida, R; Nakanishi, Y
Abstract : Aims: The perforin mediated pathway is the major pathway of cytotoxicity induced by activated T cells and natural killer cells, and may be involved in the development of pulmonary fibrosis. Methods: Perforin and granzyme B expression were examined in idiopathic pulmonary fibrosis by means of immunohistochemistry, and perforin knockout mice were used to examine whether or not perforin mediated cytotoxicity participates in the pathophysiology of bleomycin induced pneumopathy. Results: Perforin and granzyme B expression were upregulated in infiltrating lymphocytes in lung tissue from patients with idiopathic pulmonary fibrosis compared with normal lung parenchyma. Perforin and granzyme B expression were upregulated predominantly in infiltrating mononuclear cells after bleomycin instillation in wild-type mice. Although the development of bleomycin induced pneumopathy was not completely prevented, the pathological grade of inflammation and fibrosis, and the number of apoptotic cells in lung tissue, were significantly decreased in perforin knockout mice compared with wild-type mice. Conclusions: These results suggest that perforin mediated apoptosis may be associated with the pathophysiology of lung injury and fibrosis.